Effects of exercise training on sprint and vertical jump performances among athletes from intermittent sports - Koh, Jing Jing (2017)
There has been an increasing number of reports stating that resistance training aids sport performances. The purpose of this study was to investigate the effects of deadlift training (DT) on sprint and vertical jump (VJ) performances among Ultimate Frisbee (UF) athletes. It was hypothesized that DT will improve sprint and VJ performances. Eight experienced (age, 23.382.07 years; height, 1.700.05m; weight, 61.183.85kg) UF male participants were recruited and randomly assigned to either the control (n=4) or the training group (n=4). Participants were aged 21-30 years, and have participated in UF competitively for minimum of 2 years with no history of back, neuromuscular or musculoskeletal injury. Participants completed bioelectrical impedance analysis, sprint and VJ assessments as pre-test, followed by 12 training sessions; twice per week for 6 weeks. Same assessments were conducted for post-test. All participants performed exercises such as jogging on the treadmill at speed 5.5 to 7.5kph for 5 minutes, 20 jumping jacks, 10 high knees and 10 walking lunges. After resting, participants in training group performed 5 sets of 5 repetitions supervised DT at an intensity of 85% of 1 repetition maximum (RM). Results showed significant improvement between pre- and post-tests for both sprint and VJ assessments in the training group (sprint: p = 0.012, VJ: p = 0.009). There were no significant differences between the two groups for both pre- and post- tests. This concluded that DT may not be beneficial to improve performance and improvement in performance might be observed if the training intervention period is extended.